Advertising industry: Trends oppurtunities and challenges with specisl emphasis of Chinese tourism - Misko Dzidrov (UTMS Journal of Economics, 2010)
Now day advertising has craftily become an inescapable companion of modern life that we can't escape and avoid it, truly it's an intrinsic part of our daily lives. Advertising affects everyone's life and influences many purchasers. Consumer turns to advertising for its informativeness, as well as its entertainment value. In November 2001, China joined the World Trade Organization (WTO) and became a formal member of the free trade club. China's accession to the WTO came after the country had economic reforms and significant growth of Chinese economy. In the same period advertising start booming in China (early 1979); it has become dramatically an increasing important business, industry, and custom artefact in the country. A lot of researches have been made on advertising industry in the west and are one of everyday activity in the current market, but researches about Chinese advertising about tourism market has generally been limited to journal articles. The purpose of this research is to: Investigate how consumers read and understand advertising in China, mainly tourism advertising; To learn how Chinese consumers react to TV and print advertisements; Examine what role advertising playing in marketing and how it perused people of China - moreover which channel is most preferable to advertise tourism offers in Chinese society.
Keywords: 330; China advertising industry; marketing in tourism; advertising channels